1983
DOI: 10.1038/ki.1983.101
|View full text |Cite
|
Sign up to set email alerts
|

Acute changes in peritoneal morphology and transport properties with infectious peritonitis and mechanical injury

Abstract: Peritoneal clearance studies were performed in rats undergoing acute peritoneal dialysis. Some of these animals were then exposed to laparotomy and mechanical drying of the peritoneum. Peritoneal clearance studies were repeated at intervals up to 11 days. Another group of rats was placed on daily peritoneal dialysis and allowed to spontaneously develop peritonitis which was not treated. These rats underwent peritoneal transport studies at differing durations of infection. In all groups, animals were sacrificed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
76
1

Year Published

1989
1989
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(80 citation statements)
references
References 16 publications
3
76
1
Order By: Relevance
“…The production of collagen is stimulated also by serum and peritoneal fluid of patients with peritonitis and is prevented by anti-HGF antibody. The collagen proteins produced by mesothelial cells are type III and type I (␣1) 3 , i.e., the two types, especially type III, that are assembled as fibrotic tissue in organs exposed to chronic inflammation. 39 The release of HGF during peritonitis and the evidence that HGF acts on mesothelial cells suggest that HGF influences in several ways the process of healing of the peritoneum, especially in patients undergoing peritoneal dialysis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The production of collagen is stimulated also by serum and peritoneal fluid of patients with peritonitis and is prevented by anti-HGF antibody. The collagen proteins produced by mesothelial cells are type III and type I (␣1) 3 , i.e., the two types, especially type III, that are assembled as fibrotic tissue in organs exposed to chronic inflammation. 39 The release of HGF during peritonitis and the evidence that HGF acts on mesothelial cells suggest that HGF influences in several ways the process of healing of the peritoneum, especially in patients undergoing peritoneal dialysis.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of peritonitis was based on clinical signs (cloudy peritoneal fluid, abdominal pain), leukocyte count Ͼ100/ mm 3 and positive culture in peritoneal fluid. The two groups of patients were matched for age, time on CAPD, number of peritonitic episodes, and index of dialysis adequacy (KT/V).…”
Section: Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have reported that uremia is associated with inflammation of the peritoneal membrane [12]. Histologically, acute peritonitis can cause morphological damage to the peritoneum [10,13]. Detachment and disintegration of mesothelial cells is observed, along with the appearance of fibrin exudation and numerous infiltrating cells, ultimately resulting in internal structures becoming unrecognizable [6].…”
Section: Introductionmentioning
confidence: 99%
“…However, the local accumulation of leukocytes during peritonitis is associated with marked structural changes of MC, characterized by a cuboid cell shape, hyperplasia of the rough endoplasmatic reticulum, and discontinuity of cell-cell contacts [7, 8, 9]. MC injury is thought to be caused by activated and adherent polymorphonuclear leukocytes which release a number of protease enzymes and free radicals (O – 2 , H 2 O 2 , and HO – ) to create an injurious microenvironment [10, 11].…”
Section: Introductionmentioning
confidence: 99%